Deep brain stimulation for treatment-refractory obsessive-compulsive disorder should be an accepted therapy in Australia. (May 2022) - Mosley, Philip E; Velakoulis, Dennis; Farrand, Sarah; Marsh, Rodney; Mohan, Adith; Castle, David; Sachdev, Perminder S
Deep brain stimulation has shown promise for the treatment of severe, treatment-refractory obsessive-compulsive disorder. With the recent publication of the first Australian, randomised, sham-controlled trial of deep brain stimulation for obsessive-compulsive disorder, there are now four placebo-controlled trials demonstrating the efficacy of this therapy. Together with recent data identifying a biological substrate of effective stimulation that can predict response and that has been successfully reproduced, studies comparing and finding equivalent efficacy among different targets, as well as recent, large, open trials supporting the long-term effectiveness of deep brain stimulation, we argue that this should now be considered an accepted therapy for a select group of patients in the Australasian setting. We call on the Royal Australian and New Zealand College of Psychiatrists to revise their memorandum describing deep brain stimulation for obsessive-compulsive disorder as an ' experimental ' treatment and recognise that it has proven efficacy. We stress that this should remain a therapy offered only to those with high treatment-refractory illnesses and only at specialised centres where there is an experienced multidisciplinary team involved in work-up, implantation and follow-up and also where frameworks are in place to provide careful clinical governance and ensure appropriate fully informed consent.